The Effect of Work Demands on Work Engagement with Job Crafting as a Moderating Variable in Minimarket Employees - Zalsabila Hasianka; Hilwa Anwar; Rahmawati Syam (Polteknik Ilmu Pemasyarakatan, 2023)
This study aims to examine the role of job demands on work engagement moderated by convience store employes job crafting. In this quantitative study, there are three measuring tools were used to collect the data, the ultrech work engagement scale (UWES), Job Demands-Resource Questionnare, and Job crafting Scale. The subject were 120 convience store in Makassar by accidental sampling. The analytical method used is Moderated Regression Analysis (MRA). The result of this study indicate that there are positive significant affect of job demand on work engagement (p=0.001 and t=3.260) and job crafting cannot moderated the affect of job demands on work engagement (p=-0.006). The result is, job demands has positive significant affect on work engagement, but job crafting cannot moderated the affect of job demands on work engagement.